Structure of human GABA(B) receptor in an inactive state - Park, Jinseo (Nature, 2020)
Human GABA(B) G protein-coupled receptor (GPCR), a member of the class C family, mediates inhibitory neurotransmission and is implicated in epilepsy, pain, and addiction(1). A unique GPCR known to require heterodimerization for function(2–6), its two subunits, GABA(B1) and GABA(B2), are structurally homologous but perform distinct and complementary functions. GABA(B1) recognizes orthosteric ligand(7,8), while GABA(B2) couples with G protein(9–14). Each subunit is characterized by an extracellular Venus flytrap (VFT) module, a descending peptide linker, a seven-helix transmembrane (TM) domain, and a cytoplasmic tail(15). Whereas the VFT heterodimer structure has been resolved(16), the structure of the full-length receptor and its transmembrane signaling mechanism remain unknown. Here we present a near full-length structure of the GABA(B) receptor, captured in an inactive state via cryo-electron microscopy (EM). Our structure reveals multiple ligands pre-associated with the receptor, including two large endogenous phospholipids embedded within the TM domains to maintain receptor integrity and modulate receptor function. We also identify a novel heterodimer interface between TM helices 5 and 3 of both subunits, which serves as a signature of the inactive conformation. A unique ′intersubunit latch′ within this TM interface maintains the inactive state, and its disruption leads to constitutive receptor activity.